The Influence of Ideological and Political Education on Students’ Self-Harvest in Physical Education Courses in Colleges - Yile Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
To encourage physical education teachers to prioritise students' physical education as the central focus of interaction, foster a shift towards student-centred teaching, enhance enthusiasm for college physical education courses, and integrate moral education principles into the physical education curriculum. This study examined the impact of teacher-student interaction on students' self-cultivation in ideological and political education within the physical education curriculum at the college level through the construction of an equal education model. The data was entered into the system using SPSS 23.0 and Amos 26.0 statistical software to assess the reliability, validity, and research hypothesis of the model. The impact of physical exercise, personal exercise, sports organisations, sports events, and teacher consultation were found to be 0.944%, 0.93%, 0.897%, and 0.935%, respectively. Teacher-student interaction is crucial in physical education (PE) classes, particularly for sports education and promoting growth. The presence of sports facilities and equipment significantly influences teacher-student interaction. Therefore, it is essential to enhance the development of PE courses, improve the availability of physical education resources, update teaching approaches, implement innovative models of PE classes, and enhance students' sense of achievement to facilitate effective teacher-student interaction.